Hubungan Dukungan Suami dengan Pemanfaatan Kelas Ibu Hamil di Wilayah Kerja Puskesmas Harapan Raya Pekanbaru - Yusmaharani, Yusmaharani (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
One of the program to improve the health of pregnant women is by holding Class of pregnant women, itâsmeans to learn together about the health of pregnant women. In 2015 from 20 public health centers in Pekanbaru there are only 3.7 percent of pregnant womens classes, which should reach 80 percent of pregnant womens classes. This happens because many classes of pregnant women are formed by public health center but no mothers are participating in the class. This study aims to determine the factors associated with the utilization of the class of pregnant women. The design of this study is cross sectional with a large sample of 211 people. Sampling method used systematically random sampling. Data analysis was done by univariat and bivariate. The resultsr research was obtained by mothers who do not use the class of pregnant women as much as 163 people (77 percent). The result of bivariate analysis showed that P value less than 0,001 (OR: 10,6, C.I.95 percent: 3,864 to 29,124) meaning that there is a significant correlation between Support by Husband and Utilization of Maternal Class. The conclusion in this research that there is a relationship between support by husband with the utilization of pregnant mother class. Keyword:Support by Husben, Utilization, Pregnant.